Combining orthogonal plant and non-plant fatty acid biosynthesis pathways for efficient production of microbial oil enriched in nervonic acid in Yarrowia lipolytica. (June 2023) - Wang, Kaifeng; Lin, Lu; Wei, Ping; Ledesma-Amaro, Rodrigo; Ji, Xiao-Jun
Graphical abstract: Highlights: Alternative strategy for nervonic acid-enriched plant oil production is developed. Orthogonal plant and non-plant nervonic acid synthetic pathways are constructed. MoLPAAT from Malania oleifera is identified to be specificity for nervonic acid. The highest titer of nervonic acid at 13.56 g/L is achieved in Yarrowia lipolytica . Abstract: Nervonic acid has proven efficacy in brain development and the prevention of neurodegenerative diseases. Here, an alternative and sustainable strategy for nervonic acid-enriched plant oil production was established. Different β-ketoacyl-CoA synthases and heterologous Δ15 desaturase were co-expressed, combined with the deletion of the β-oxidation pathway to construct orthogonal plant and non-plant nervonic acid biosynthesis pathways in Yarrowia lipolytica . A "block-pull-restrain" strategy was further applied to improve the supply of stearic acid as the precursor of the non-plant pathway. Then, lysophosphatidic acid acyltransferase from Malania oleifera ( Mo Lpaat) was identified, which showed specificity for nervonic acid. Endogenous LPAAT was exchanged by MoLPAAT resulted in 17.10 % nervonic acid accumulation. Finally, lipid metabolism was engineered and cofactor supply was increased to boost the lipid accumulation in a stable null-hyphal strain. The final strain produced 57.84 g/L oils with 23.44 % nervonic acid in fed-batch fermentation, which has the potential to substitute nervonic acid-enriched plant oil.